A comparative study of different winemaking by-products derived additives on oxidation stability, mechanical and thermal proprieties of polypropylene. (March 2018) - Nanni, A.; Messori, M.
Abstract: Three different solid wine wastes (peels, seeds and stalks) have been mixed with polypropylene (PP) and tested as stabilizers. Their stabilizing activity has been compared with that of a commercial tannin extract powder, rich in polyphenol. Thermogravimetric analysis, Oxidation Induction Time and Oxidation Onset Temperature measurements have been conducted to investigate the thermo-oxidative stability. Tensile tests, Dynamic Mechanical Analysis and Differential Scanning Calorimetry have been conducted on the samples in order to evaluate the effect of the additives also on the thermal and mechanical properties. Scanning Electron Microscopy have been used to assess the adhesion and distribution of the wine-wastes additives within the PP matrix. Experimental results evidence that all three wine-wastes derived additives do not significantly change the mechanical and thermal properties of PP, meanwhile they enhance its thermal stability. Moreover, the expectation to obtain better results with the commercial tannin extract has not been achieved. The obtained results show how wine wastes can be effectively used as polymer stabilizers and represent a valid alternative because of theirs environmental and cost-effects advantages. Highlights: Wine-waste derived additives very effective for improving the thermal stability of the polypropylene (PP). No negative changes in mechanical proprieties with respect to pristine PP. No need of waste separations. Wine by-products additives as low-cost stabilizers suitable for large-scale processes.